基于ADAMS高炉堵渣机自调结构及仿真分析 - 杜研; 安培文 (Jixie chuandong)
Some main problems of stopper are found with motionsimulation analysis based on ADAMS software,and then a stopper is designed with self-adjustable structure without overconstraints.Simulation results show that the performance of the stopper is improved with the benefit of more reliable working process.It is indicated that the self-adjustable structure of mechanism has the engineering practical value and great prospect.